Trajes del teatro del mundo: vestimenta, sujetos y diferencia americana en la primera modernidad - Alejandra Vega (Nuevo mundo - Mundos Nuevos, 2014)
Costume books were a genre of editorial production in the second half of the sixteenth century. Composed of illustrations and texts, they proposed an elucidation of the various nations of the world through the description of dress. Issued from various centers of editorial production in Western Christendom, these books- despite their differences- share formal characteristics and a set of ideas concerning the relationship between dress or costume and the status of the individual. The costume books include representations of the dress of the populations of the Americas. In this text we discuss the forms that this inclusion takes. To do this, instead of focusing exclusively on the iconography, we analyze the way in which the ideas that organize these books are applied specifically to American inhabitants: the hierarchization and specification of social condition as it is expressed in dress; the relationship between nation, territory and costume; and the mutation in forms of dress. In all these matters, we find an attenuation or indeterminacy. American space representation and the colonial construction of its population are marked by this condition.